Digital Technology And Adolescent Behavior Transformation: The Challenges Of Moral Education In Schools - Halen Dwistia; Tanzania, Aulia; Anisak, Siti Darojatun; Wantika, Wantika (JURNAL PEDAGOGY, 2024)
Digital technology has become an integral part of adolescent life, providing seamless access to information and social interaction. However, their impact on their behavior and moral values is a serious concern, especially in the context of education. This research is motivated by the phenomenon of increasing negative behaviors, such as cyberbullying and reduced empathy, the attitude of togetherness, tolerance, and helping others, which is influenced by excessive use of social media. Regarding the above problems, based on the review literature, it is known that there is still a lack of holistic studies that integrate the influence of digital technology on adolescent morality with relevant moral education strategies in schools. The method used qualitatively with a literature review approach aims to analyze, synthesize, and assess relevant studies or literature to gain an in-depth understanding of the influence of digital technology on adolescent morality with relevant moral education strategies in schools. The purpose of this study is to reveal the influence of digital technology on the transformation of adolescent behavior and evaluate the challenges faced by moral education in shaping better adolescent character. The results of this research are expected to make a practical contribution in formulating more effective moral education strategies in schools, as well as providing recommendations for parents and educators in directing the wise use of digital technology.